2017
DOI: 10.1038/tp.2017.28
|View full text |Cite
|
Sign up to set email alerts
|

Infant frontal EEG asymmetry in relation with postnatal maternal depression and parenting behavior

Abstract: Right frontal electroencephalogram (EEG) asymmetry associates with negative affect and depressed mood, which, among children, are predicted by maternal depression and poor parenting. This study examined associations of maternal depression and maternal sensitivity with infant frontal EEG asymmetry based on 111 mother-6-month-infant dyads. There were no significant effects of postnatal maternal depression or maternal sensitivity, or their interaction, on infant EEG frontal asymmetry. However, in a subsample for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 75 publications
4
34
0
1
Order By: Relevance
“…In addition, only female adolescents with early life stress show a positive association between amygdala‐ventromedial prefrontal cortex (vmPFC) functional connectivity and depressive symptoms (Burghy et al, ). Similarly, a recent study suggests that influences of maternal depressive symptoms are gender‐specific in a certain developmental time window (Wen et al, ). Greater prenatal maternal depressive symptoms were associated with larger right amygdala volume in girls, but not in boys (Wen et al, ).…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…In addition, only female adolescents with early life stress show a positive association between amygdala‐ventromedial prefrontal cortex (vmPFC) functional connectivity and depressive symptoms (Burghy et al, ). Similarly, a recent study suggests that influences of maternal depressive symptoms are gender‐specific in a certain developmental time window (Wen et al, ). Greater prenatal maternal depressive symptoms were associated with larger right amygdala volume in girls, but not in boys (Wen et al, ).…”
Section: Introductionmentioning
confidence: 89%
“…Greater prenatal maternal depressive symptoms were associated with larger right amygdala volume in girls, but not in boys (Wen et al, ). Increased postnatal maternal depressive symptoms were associated with greater water diffusivity in right amygdala only in girls (Wen et al, ). These findings demonstrate the vulnerability of the amygdala's emotional perception and regulation networks to maternal depression and such vulnerability may be specific to gender.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the same cohort, we previously found that postnatal maternal depressive symptoms altered the volume, microstructure, and functional connectivity of the amygdala in girls (Soe et al, 2018;Wen, Soe et al, 2017). Using the same cohort, we previously found that postnatal maternal depressive symptoms altered the volume, microstructure, and functional connectivity of the amygdala in girls (Soe et al, 2018;Wen, Soe et al, 2017).…”
Section: Discussionmentioning
confidence: 73%
“…In this study, we aimed to investigate this hypothesis by examining of the lOFC and mOFC functional and structural networks in relation with postnatal maternal depressive symptoms in children at age 4 and 6 years and their contribution to child's approach/withdrawal behavior. Given considerable evidence for sexually dimorphic associations between maternal mental health and neurodevelopmental outcomes (Soe et al, 2018;Wen, Soe et al, 2017), we explored our hypothesis in boys and girls, respectively, to elucidate potential sex-dependent OFC in response to maternal depressive symptoms in early life. This was mainly because of roles of the lOFC and mOFC in emotion and reward processing and because maternal depression promotes forms of parenting (Field et al, 2004;Fleming, Flett, Ruble, & Shaul, 1988) that enhance stress reactivity, social withdrawal, and inattention (Bruder-Costello et al, 2007;Caspi, Moffitt, Newman, & Silva, 1996;Cote et al, 2009).…”
mentioning
confidence: 99%